Seasonal gonadal changes, spawning and condition index of oyster Crassostrea madrasensis (preston) in the Korampallam creek, Tuticorin - Palaniswamy, Rani (Indian Journal of Fisheries, 2011)
Studies on seasonal changes of the gonadof oysters are useful in spat fall predictionand also in selecting the broodstock forhatchery production of the seed. The gonadalcondition of the oysters Crassostreamadrasensis in different seasons was reportedby Rao (19S6), Durve (196S), Stephan(1980), Rajapandian and Rajan (1983) andNarasimham (1987). Nair and Mahadevan(1983) elucidated the various aspects in oysterculture carried out in the Tuticorin bay.The present study gives the results on theseasonal changes in the gonad and meatcondition of oysters collected from theKorampallam creek, near Tuticorin.